Bentonite as an engineered barrier material for nuclear waste repository - Geotechnical perspectives, key properties, knowledge gaps, and opportunities - Dong-Hwa Noh; Seunghee Kim; Jose Maria Ferdinand Victoria Calaunan; Yuan Feng; Jongwan Eun; Yong-Rak Kim (Nuclear Engineering and Technology)
The deep geological repository is a widely recognized solution for isolating high-level radioactive waste (HLW). Bentonite, with its low hydraulic permeability, high swelling property, and strong sorption capacity, serves as a key engineered barrier material to prevent radioactive leakage. While extensive studies have examined its thermo-hydro-mechanical (THM) properties, some aspects still remain unclear, requiring further research to secure the long-term stability of bentonite. This paper presents a comprehensive review of bentonite's role in deep geological repositories from a geotechnical perspective. It first review the basics of montmorillonite, the primary mineral of bentonite, and its unique pore structure. Next, it examines past and ongoing nuclear waste disposal projects worldwide, highlighting key findings. Furthermore, the essential engineering properties of compacted bentonite blocks, including thermal and hydraulic conductivity, swelling pressure, water retention capacity, and mineral transformation, are reviewed. Lastly, this paper discusses the challenges, opportunities, and future research needs for optimizing bentonite's performance as a barrier material in geological disposal systems. By consolidating past research and identifying knowledge gaps, this review aims to provide insights into improving the long-term efficiency and stability of bentonite-based barrier systems for HLW containment.